S.I.R.I.A. - The information system of Italian research in Antarctica - Di Bono, Maria Grazia; Martinelli, Massimo; Salvetti, Ovidio; Benedetti, E.; Castorina, Mario; Damiani, A.; Piervitali, E.; Rafanelli, C. (2004)
The Italian Research in Antarctica Information System Project (Italian acronym SIRIA) is devoted to the collection and dissemination of information on Italian research in Antarctica. It is focused to preserve scientific data of PNRA (Antarctic Research National Programme), dating from as long ago as 1985. In addition SIRIA constitutes the Italian contribution to the Antarctic Master Directory, the international database of Antarctic data set descriptions, endorsed by SCAR. This work presents the aim and the activity of the SIRIA Project.